Pengesanan kerosakan gentian dalam rangkaian FTTH menggunakan sistem pengesanan kerosakan terpusat (CFDS) - Mohammad Syuhaimi Ab-Rahman,; Ng, Boon Chuan; Kasmiran Jumari, (2009)
Issues with fiber fault in fiber to the home (FTTH) customer access network often become a challenge to the network service providers. The most important issues troubled the service providers and customer premises are regarding the service reliability and safety. Conventionally, optical time domain reflectometer (OTDR) is used to detect the fiber fault and address the failure location in FTTH upwardly from customer sides toward central office (CO). However, OTDR can only display a measurement result of a testing line in a time and also time and cost misspend. By looking at the stated issues, a simple, attractive and user friendly graphical user interface (GUI) is developed for Centralized Failure Detection System (CFDS) based on MATLAB programming in this study. The developed program will be installed with optical line terminal (OLT) at the CO to centralized monitoring each optical fiber line’s status and identifying the failure location that occurs in the drop region of FTTH downwardly from CO towards customer sides. CFDS is interfaced with OTDR to accumulate every network testing result to be displayed on a single computer screen for further data analyzing. The analysis results will be sent to field engineers or service providers for promptly actions.